RETRACTED: Evaluating the effect of culture filtrate of Trichoderma harzianum on the seed germination and seedling growth of Pinus sylvestris - Saleh Abdulrahman; Kalashnikova Elena; Kirakosyan Rima; Kozlov Andrey (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001